2014
DOI: 10.1177/2151458514532469
|View full text |Cite
|
Sign up to set email alerts
|

“Tiers of Delay”

Abstract: Anticoagulation reversal is a common cause of operative delay. We sought to establish for the first time the impact this has on best practice tariff (BPT) for patients with hip fracture admitted on warfarin. All patients with hip fracture treated operatively over a 32-month period were reviewed. Basic demographics, time to theater, length of stay, and mortality were recorded for all patients. Independent samples t-tests were used to identify statistically significant differences between patients on warfarin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 27 publications
(39 reference statements)
2
22
0
Order By: Relevance
“…This delay has been reported in previous studies [7, 8, 16, 24], although our study is the first, to our knowledge, showing the same association after regression analysis using these prognostic factors. Ryan et al [21] conducted a study with more than two million patients sustaining a fractured neck of the femur and reported that a time to the operating room in excess of 48 hours resulted in higher mortality, with an OR of 1.13 for the delayed group after controlling for multiple prognostic factors including comorbidity.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This delay has been reported in previous studies [7, 8, 16, 24], although our study is the first, to our knowledge, showing the same association after regression analysis using these prognostic factors. Ryan et al [21] conducted a study with more than two million patients sustaining a fractured neck of the femur and reported that a time to the operating room in excess of 48 hours resulted in higher mortality, with an OR of 1.13 for the delayed group after controlling for multiple prognostic factors including comorbidity.…”
Section: Discussionsupporting
confidence: 90%
“…Ranhoff et al [16], in a 2011 study of 1192 patients with hip fracture, found longer length of stay for warfarin users compared with nonusers. Conversely, Eardley et al [8], in a [2014 study of 1024 patients, showed no association between length of stay and the use of warfarin at the time of admission for hip fracture. Our study differs from both of these in that we have controlled for age, sex, ASA score, AMTS, WAI, fracture type, and operation type in our analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eardley et al 11 studied the time to surgery of the warfarinised patients affected with hip fractures and the economic impact on the best tariff practice (BTP) over the study period of 32 months.…”
Section: Resultsmentioning
confidence: 99%